The complete mitochondrial genome of the Kandelia obovata Sheue, H.Y.Liu & J.W.H.Yong (Rhizophoraceae) - Xiuming Xu; Chengcheng Hou; Yingjia Shen (Mitochondrial DNA. Part B. Resources, 2023)
AbstractKandelia obovata Sheue, H.Y.Liu & J.W.H.Yong is one of the most cold-resistant true mangrove species, and it is widely distributed from the South China Sea to southern Japan. In the current study, the complete mitochondrial genome sequence of K. obovata was assembled using Illumina reads. It is the first mitochondrial genome of the Kandelia genus within the family Rhizophoraceae to be sequenced. The mitochondrial genome size is 312,146 bp with a total of 49 predicted genes, including 29 protein-coding genes, 17 transfer RNA genes, and 3 ribosomal RNA genes. The overall GC content of the genome is 41.87%. A phylogenetic tree constructed using nine complete mitochondrial genomes revealed that K. obovata is more closely related to Bruguiera species. This study enriches the plastid genome of Kandelia, furnishing valuable genetic insights for the investigation of evolutionary and population genetics in Kandelia and other mangrove species.